2019
DOI: 10.1016/j.pharmthera.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and sarcopenia: The next-generation of personalized oncology and pharmacology?

Abstract: Body composition has gained increasing attention in oncology in recent years due to fact that sarcopenia has been revealed to be a strong prognostic indicator for survival across multiple stages and cancer types and a predictive factor for toxicity and surgery complications. Accumulating evidence over the last decade has unraveled the "pharmacology" of sarcopenia. Lean body mass may be more relevant to define drug dosing than the "classical" body surface area or flat-fixed dosing in patients with cancer. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
118
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 317 publications
(260 reference statements)
0
118
0
12
Order By: Relevance
“…It has been shown that lean body mass correlates better with pharmacokinetics and drug toxicities . The measurements of body composition other than BMI using readily available CT images might help guide individualized treatment and supportive care …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that lean body mass correlates better with pharmacokinetics and drug toxicities . The measurements of body composition other than BMI using readily available CT images might help guide individualized treatment and supportive care …”
Section: Discussionmentioning
confidence: 99%
“…These cut‐offs were established from Canadian population with respiratory or gastrointestinal tract cancer. However, the body composition may be affected by the type and stage of the cancer and by demographic factors such as age, sex, and ethnicity . The BMI of the Asian population is relatively low compared with that of the Canadian population .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations